Analysis of '5.29' blast furnace burst accident of Fangda special steel. Issue 1 (December 2020) - Yang, Chengcheng; Kong, Xiangzhi; Zhang, Lijing; Tao, Gang
Abstract: On May 29, 2019, a blast furnace explosion occurred in the iron making plant of Fangda Special Steel Technology Co., Ltd. in Qingshanhu District, Nanchang City, Jiangxi Province. The corrugated compensator of No.2 blast furnace gas riser burst, resulting in 6 deaths, 4 injuries and direct economic losses of more than 27.24 million yuan. Through the analysis of the amount of water drawn from the top of blast furnace, this paper concludes that this is a physical explosion caused by overheating, rapid boiling expansion and over-pressure of liquefied water. Through the qualitative evaluation of the accident by Bow-tie model, the specific causes and consequences are analyzed, and the physical model is used to carry out a further quantitative analysis of the consequences, the hazard area is determined, and the countermeasures to prevent the burst accident of corrugated compensator are put forward, which is helpful to prevent the recurrence of such accidents.